2015
DOI: 10.1080/10494820.2015.1057743
|View full text |Cite
|
Sign up to set email alerts
|

The benefits and barriers of using virtual worlds to engage healthcare professionals on distance learning programmes

Abstract: Using the delivery of a large postgraduate distance learning module in bioethics to health professionals as an illustrative example, the type of learning activity that could be enhanced through delivery in an immersive virtual world (IVW) was explored. Several activities were repurposed from the "traditional" virtual learning environment into the IVW, providing insight into the pedagogical affordances of each environment. Voluntary classes, which were held each week over the 12-week module, were designed to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…None of the included reviews were scored as a level 4 outcome27; thus, it was difficult to determine whether the learning outcomes were attributable to the training or institutional performance over time. Concerning facilitators and barriers to metaverse use, the former included instructor ability and technical competency, as well as participant engagement,29,34,38 whereas the latter included lack of student comfort, technological limitations, and inconsistency in implementation,20,30,31 which correlate with challenges to VW use reported by Hack 12…”
Section: Discussionmentioning
confidence: 99%
“…None of the included reviews were scored as a level 4 outcome27; thus, it was difficult to determine whether the learning outcomes were attributable to the training or institutional performance over time. Concerning facilitators and barriers to metaverse use, the former included instructor ability and technical competency, as well as participant engagement,29,34,38 whereas the latter included lack of student comfort, technological limitations, and inconsistency in implementation,20,30,31 which correlate with challenges to VW use reported by Hack 12…”
Section: Discussionmentioning
confidence: 99%
“…17. Work Commitment (WC) -Students with work commitment far more likely to dropout (Hack, 2016). Literature has reported that students often miss classes and deadlines due to their work commitments (Trede, Markauskaite, McEwen, & Macfarlane, 2019).…”
Section: Family Commitments (Fc) -mentioning
confidence: 99%
“…(15) Cost of using technology (CUT) -CUT, similar to barrier 13, can hinder adoption of e-learning system (Gupta and Jain, 2014) (Hack, 2016). The literature has reported that students often miss classes and deadlines due to their work commitments (Trede et al, 2019).…”
Section: Understanding the Tipec Individual Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are many advantages and opportunities in the paradigm of online education, it should be noted that online education is not free of challenges and shortcomings. Undoubtedly, the existing channels of student engagement (Fuchs 2020b), ability to meet learning outcomes (Hack 2016), and participation of low-performing students (de Oliveira et al 2018) were just a few of the challenges that earlier studies identified. However, based on the nature of the significant changes that emergency remote teaching (ERT) could bear, there was potentially a new set of challenges that yet needed to be identified.…”
Section: Introductionmentioning
confidence: 97%